Kita & Undang-Undang : Program UiTMLaw bersama BERNAMA Radio - UiTM, Faculty of Law (Faculty of Law, 2021)
It is indeed such a great apportunity for group of UiTMLaw lecturers collaborating with BERNAMA Radio's Bahasa Melayu radio titled 'Kita dan Undang-Undang' starting from 6 september untul 13 disember 2021. This slot consists of 13 episodes beginning at 9.30 am every Monday discussing various issues on legal development from different aspects of law including Constitutional Law, Contract Law, Cyber Law, Criminal Law, Consumer Law, Employment Law and Environmental Law.